Individual and Organizational Impact of Enterprises Resources Planning System in Healthcare Sector - ASAD ILYAS; MUHAMMAD FIAZ; ASMA TAYYABA (Mehran University Research Journal of Engineering and Technology, 2016)
Use of ERPS (Enterprise Resource Planning System) in healthcare sector has positive impacts. The purpose of this research is to find out the individual and organizational impact in healthcare sector. Hypotheses were postulated that the use of ERPS has positive individual and organizational impacts. A research questionnaire was used to test these hypotheses which have twelve dimensions for both impacts. This instrument was adopted from literature and self-administrated to 504 individuals with response rate of 60% and only 56% of questionnaires were used. The results of this study revealed that the use of ERPS has positive individual and organizational impacts. This study will help the healthcare organizations to find out impacts of ERPS in healthcare sector and also to better understand the individual and organizational impacts